Islamic Economic Perspective on Factors Influencing Cassava Farmers’ Income in Gunung Sugih, Central Lampung - L. Lusyani; Z. Zulaikah; Agus Kurniawan (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study analyzes how land area, production costs, and production output affect cassava farmers’ income in Gunung Sugih, Central Lampung, through a quantitative associative design. Data were collected using closed-ended Likert questionnaires, interviews, and observations from cassava farmers (final sample size: [N=165], determined via Cochran’s formula with a 10% margin of error). Instrument validity and reliability were confirmed; Cronbach’s Alpha was 0.651 (land area), 0.700 (production costs), 0.779 (production output), and 0.813 (income). Multiple linear regression shows that all three variables have positive and significant effects on income (p<0.05), with production output being the most influential factor. The model explains 72.6% of income variation (R²=0.726). From an Islamic economic perspective, halal financing, honest transactions, efficient cost management, and commitment to communal welfare strengthen the effectiveness of these technical factors and contribute to blessed income. Policy implications include support for sharia-compliant financing, input access, and farmer training focused on productivity and efficiency.